Simulating and Contrasting the Game of Open Access in Diverse Cultural Contexts: A Social Simulation Model - Terán, Oswaldo; Dávila, Jacinto (Publications (Basel), 2023)
Open Access is a global cause with the aim of allowing unrestricted access to all scientific research output in electronic formats. This paper presents a model for simulating the game of interests behind this cause in order to investigate ways of promoting the practice of open access. The model represents the following actors: Academics, Administrators, Funders, Publishers and Politicians. Five scenarios were developed to represent both realistic and ideal, interesting, situations. The model was developed using the SocLab platform—a formalization of the sociology of organizational action. It is based on previous descriptions of the game and expert knowledge. A structural analysis permits us to examine the properties of the sub-model behind each scenario. The results corroborate certain intuitions about the scenarios representing realistic cases, e.g., they indicate that publishers, being isolated in their interests, are subject to strong pressures from other actors, who have a circumstantial alliance. Administrators take an intermediate stance in all scenarios. The best scenarios for open access are those in which Politicians and Funders clearly support the cause by expressing mandates in that direction, backing academics. Surprisingly, the model shows that it is in the Publishers’ interest not to take an extremist position against open access.